Explantation of a sutureless scleral fixated Carlevale intraocular lens due to calcification: a clinical and laboratory report - Panos S. Gartaganis; Panagiota D. Natsi; Sotirios P. Gartaganis; Petros G. Koutsoukos; Evangelos Manousakis; Efthymios Karmiris (BMC Ophthalmology, 2023)
Abstract Background Hydrophilic intraocular lens opacification is a rare complication due to calcification. With current new surgical techniques, including lamellar endothelial keratoplasty and vitrectomies, this irreversible complication is becoming more common. In this case study, we present clinical and laboratory features of a case of Carlevale hydrophilic acrylic IOL calcification. Case presentation Observational case report of a single incident case. An 83-year-old man was referred to our ophthalmic department complaining of right eye vision blurring for six months. Slit-lamp biomicroscopy revealed IOL opacification. Deposits of calcium phosphate were found both on the IOL’s surface and inside it, according to thorough investigation using optical, scanning electron microscopy (SEM), and energy-dispersive X-ray (EDX) spectrometry. Conclusions To the best of our knowledge, this is the first case to describe the laboratory evidence of Carlevale hydrophilic IOL calcification, suggesting possible explanation mechanisms based on underlying pathology and surgical technique. It reminds us that these findings suggest that physicians should be aware of possible hydrophilic IOL calcification.